PENINGKATAN AKURASI PENGAMBILAN FOTOGRAMETRI DENGAN JALUR TERBANG AUTOPILOT HEXACOPTER - Al, Al; Fajrin, Fajrin; Karim, Abdul (ITP Press, 2024)
The utilization of Hexacopters represents a method for large-scale mapping that is faster and more efficient, allowing for time savings compared to conventional survey methods. With GPS/GLONAS support, mapping data collection becomes easier and safer, facilitated through the design of flight paths using compatible software. The real-world flight safety of Hexacopters is crucial, especially in close encounters with other aircraft. In photogrammetry tasks, careful flight path planning is necessary to ensure high-quality photo outcomes. Designing flight paths using autopilot and adjusting the aircraft's speed control parameters are essential for facilitating identification and obtaining more accurate data. This approach aims to achieve stability and efficiency in photogrammetry flight missions.To evaluate the accuracy of the Hexacopter imaging mapping system, flights are conducted independently with an RGB camera flown at the testing location. Flight missions and data acquisition are meticulously planned in the laboratory, covering the area of interest (AOI), Ground Sampling Distance (GSD), and understanding the intrinsic parameters of the installed digital camera. By setting the image scale, camera focal length, and flight height, the nadir perspective of the camera is calculated to rectify overlapping longitudinal and transversal lines. The presence of GNSS/IMU is typically utilized to guide image acquisition. Test results indicate that the Ground Sampling Distance for each flight is below 1 cm/pixel.